Changes health-related quality of life in HIV-infected patients following initiation of antiretroviral therapy: a longitudinal study - Dutra,Brenda Soares (2019)
Abstract Background: Several tools have been developed to evaluate HIV health-related quality of life (HRQoL) during and after antiretroviral therapy (ART). Few longitudinal studies evaluated the effect of ART on the quality of life of HIV patients. Objective: To evaluate changes in HRQoL in HIV-infected individuals one year after initiating ART. Methods: A prospective study was conducted from May 2016 to July 2018. Data on clinical and sociodemographic characteristics of 91 HIV-infected patients were collected prior to initiation of ART and one year thereafter. Demographic and clinical data were collected and the questionnaires 36-item Short Form Health Survey (SF-36) and HIV/AIDS-targeted quality of life (HAT-QoL) were administered in both periods. Asymptomatic individuals, aged ≥18 years, were included in the study. Patients who discontinued treatment were excluded. The association between predictors of physical and mental HRQoL was analyzed by multiple linear regression analysis. Results: Patients were predominantly male (78.0%), mean age 35.3 ± 10.7 years, with no stable relationship (80.2%), and no comorbidities (73.6%). Most of the SF-36 domains improved after one year, particularly Physical Function (p = 0.0001), General Health (p = 0.0001), Social Functioning (p = 0.0001), Mental Health (p = 0.001), and Mental Component Summary (p = 0.004). HAT-QoL domains improved in the Overall Function (p = 0.0001), Life Satisfaction (p = 0.0001), Provider Trust (p = 0.001), and Sexual Function (p = 0.0001) domains. Sex (p = 0.032), age (p = 0.001), income (p = 0.007), and stable relationship (p = 0.004) were good predictors of the Physical Component Summary. Sex (p = 0.002) and stable relationship (p = 0.038) were good predictors of the Mental Component Summary. SF-36 and HAT-QoL scales presented strong correlations, except for Medication Concerns (0.15-0.37), HIV Mastery (0.18-0.38), Disclosure Worries (−0.15 to 0.07), and Provider Trust (−0.07 to 0.15). Conclusions: ART improved HRQoL after one year of use. The HAT-QoL and SF-36 correlated well and are good tools to evaluate HRQoL in HIV-infected patients on ART.